Religious pluralism and ecumenical dialogue. An analysis of the situation in the city of Pereira (2019)
The objective proposed is to perform a mappingof religious pluralism in the urban area of the cityof Pereira, with the intention of investigating thepossibilities of dialogue with Christian confessions,and propose in accordance with the Magisterium,some guidelines for ecumenical dialogue in the city.A mixed character methodology was applied becauseit includes both quantitative and qualitative methodsof a historical- hermeneutic type, using the structuralsurvey and multiple case study as tools.This work is not directly an interdisciplinarytheological reflection using a transcendental, narrative,critical hermeneutics method, but an investigationthat pretends to show -with the help of the socialsciences- the status of Christian religious plurality inthe city of Pereira (social science method) and thenindicating descriptively the Catholic teachings andguidance on Ecumenism (magisterium ), in order toreflexively propose some lines of action or guidelinesto promote ecumenical dialogue (about works,doctrine, spirituality and about life) in this region ofthe country.Among the most relevant results, it is evident thatthere is little presence of different Christian faithsand the presence of new religious movements isthree times larger than the number of parishes in theDiocese Archpriesthood of Pereira, and the mostof the faithful people interviewed belonging to themovements come from Catholicism. Besides, severalinterviewed pastors are willing to start a dialoguewith the Catholic Church and the various religiousgroups in the city. Finally, a process of acceptanceand recognition is not evidenced yet in the city, thusreligious pluralism cannot be discussed but diversityand religious plurality; and moreover, the Diocese hasnot implemented any strategy to initiate dialogueswith current religious movements existing in Pereira.